Particulate matter air pollution components and incidence of cancers of the stomach and the upper aerodigestive tract in the European Study of Cohorts of Air Pollution Effects (ESCAPE). (November 2018) - Weinmayr, Gudrun; Pedersen, Marie; Stafoggia, Massimo; Andersen, Zorana J.; Galassi, Claudia; Munkenast, Jule; Jaensch, Andrea; Oftedal, Bente; Krog, Norun H.; Aamodt, Geir; Pyko, Andrei; Pershagen, Göran; et al.
Abstract: Introduction: Previous analysis from the large European multicentre ESCAPE study showed an association of ambient particulate matter <2.5 μm (PM2.5 ) air pollution exposure at residence with the incidence of gastric cancer. It is unclear which components of PM are most relevant for gastric and also upper aerodigestive tract (UADT) cancer and some of them may not be strongly correlated with PM mass. We evaluated the association between long-term exposure to elemental components of PM2.5 and PM10 and gastric and UADT cancer incidence in European adults. Methods: Baseline addresses of individuals were geocoded and exposure was assessed by land-use regression models for copper (Cu), iron (Fe) and zinc (Zn) representing non-tailpipe traffic emissions; sulphur (S) indicating long-range transport; nickel (Ni) and vanadium (V) for mixed oil-burning and industry; silicon (Si) for crustal material and potassium (K) for biomass burning. Cox regression models with adjustment for potential confounders were used for cohort-specific analyses. Combined estimates were determined with random effects meta-analyses. Results: Ten cohorts in six countries contributed data on 227, 044 individuals with an average follow-up of 14.9 years with 633 incident cases of gastric cancer and 763 of UADT cancer. The combined hazard ratio (HR) for an increase of 200 ng/m 3 of PM2.5 _S was 1.92 (95%-confidence interval (95%-CI) 1.13;3.27) for gastric cancer, with no indication of heterogeneity between cohorts (I 2 = 0%), and 1.63 (95%-CI 0.88;3.01) for PM2.5 _Zn (I 2 = 70%). For the other elements in PM2.5 and all elements in PM10 including PM10 _S, non-significant HRs between 0.78 and 1.21 with mostly wide CIs were seen. No association was found between any of the elements and UADT cancer. The HR for PM2.5 _S and gastric cancer was robust to adjustment for additional factors, including diet, and restriction to study participants with stable addresses over follow-up resulted in slightly higher effect estimates with a decrease in precision. In a two-pollutant model, the effect estimate for total PM2.5 decreased whereas that for PM2.5 _S was robust. Conclusion: This large multicentre cohort study shows a robust association between gastric cancer and long-term exposure to PM2.5 _S but not PM10 _S, suggesting that S in PM2.5 or correlated air pollutants may contribute to the risk of gastric cancer. Highlights: Population-based cohorts from 6 European countries (227, 044 participants) Copper, iron, zinc, sulphur, nickel, vanadium, silicon and potassium in PM2.5 and PM10 were studied. Statistically significant strong association of gastric cancer with sulphur in PM2.5, but not in PM10 No association of gastric cancer with any of the other 7 elements tested No association with upper aerodigestive tract cancer